THE JUDGEâS ROLE IN ISLAMIC FAMILY LAW REFORM IN INDONESIA - Fauzi, Achmad (Islamic University of Indonesia, 2015)
There is no eternal on the earth, said the Greek philosopher Heraclitus (540- 480 BC), except the change. This famous phrase greatly affect many aspects, not least the development in the field of Islamic family law in Indonesia. Family law reform has become a sort of primary petition in every era given the dynamics of community life continues to grow rapidly. Therefore, the law is not adaptive and do not have a range beyond its time not unlike the dead artifacts in the museumâs history. While the law is the law of life that has a historical footing and strong social legitimacy in tune with the pulse of public life. Thatâs the law of political design is aspired by all the people in the coming era. Keywords : Reform, Islamic Family Law, The Judgeâs Ruling, Religious Courts, Legal Discovery, Creation of Law